Development of Guidelines for the Area-based Yield (ARBY) index insurance for rice - Raviz, Jeny; Gutierrez, Mary Anne; Laborte, Alice (International Rice Research Institute, 2024)
As part of the CGIAR Initiative on Climate Resilience (ClimBeR), the Philippine Crop Insurance Corporation (PCIC), the Philippine Rice Research Institute (PhilRice), and the International Rice Research Institute (IRRI) collaborated on the development and testing of an area-based yield (ARBY) index insurance for rice using satellite data. This partnership builds on an earlier collaboration between IRRI and PhilRice that developed and operationalized a satellite-based rice mapping and monitoring system called PRISM (Philippine Rice Information System, https://prism.philrice.gov.ph/). Historical seasonal rice yield data from PRISM was used to design the ARBY insurance product. An insurance dry run was conducted in six municipalities in the Philippines during the 2023-2024 dry season including an assessment of farmers’ willingness to pay for crop insurance. The results of the simulation were presented to partners and stakeholders in this workshop. The first day of the workshop focused on technical presentations and discussions on (1) designing the ARBY insurance product; (2) the simulation results in the six municipalities during the dry season of 2023-24; and (3) the draft ARBY insurance implementing guidelines. Participants shared insights and experiences during the insurance dry run which guided the development of the guidelines. The second day focused on the presentation of the outputs from Day 1 to municipal stakeholders including local officials and gathering their feedback.